2020
DOI: 10.1016/j.annonc.2020.08.2056
|View full text |Cite
|
Sign up to set email alerts
|

1573P Anxiety and depression in cancer patients during the COVID-19 pandemic: A single-centre study

Abstract: Background: The COVID-19 pandemic poses significant challenges for the management of patients with cancer. In our institution we adapted our delivery of outpatient systemic anti-cancer therapy (SACT) by introducing a number of 'risk-reducing' measures including pre-assessment screening. We sought to evaluate our patients' experiences of this and to gain an insight into their perception of the risks associated with COVID-19. This is a cohort of patients who are at risk of increased morbidity and mortality and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
6
14
0
Order By: Relevance
“…There were similar studies on the same dataset that we selected only one of them for the next phase. Finally, 34 articles [ 6 – 8 , 18 47 ] were included in this systematic review and of them, 16 articles [ 6 , 8 , 20 , 22 , 26 29 , 31 , 35 , 36 , 39 – 42 , 44 – 46 ] were considered for meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were similar studies on the same dataset that we selected only one of them for the next phase. Finally, 34 articles [ 6 – 8 , 18 47 ] were included in this systematic review and of them, 16 articles [ 6 , 8 , 20 , 22 , 26 29 , 31 , 35 , 36 , 39 – 42 , 44 – 46 ] were considered for meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of 34 studies had specified that patients with breast cancer were one of cancer types under study [ 18 , 19 , 22 , 24 , 25 , 28 – 30 , 32 , 33 , 38 , 40 , 41 , 43 – 47 ]. Hospital Anxiety and Depression Scale (HADS) was the most used questionnaire in the studies ( n = 10, 29.4%) [ 6 , 22 , 26 , 27 , 29 , 31 , 36 , 42 , 46 ]. Generalized Anxiety Disorder 7-item (GAD-7) [ 20 , 28 , 30 , 39 , 40 , 44 , 48 ], Self-Rating Anxiety Scale (SAS) [ 8 , 18 , 19 , 35 , 45 ] and Patient Health Questionnaire (PHQ-9) [ 20 , 40 , 44 , 48 ] were the other frequently used questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…A 24-question semi-structured questionnaire was designed to measure clinical and sociodemographic variables and the exposure level to COVID-19. This questionnaire was designed considering possible risk factors related to elevated rates of emotional distress in cancer patients and based on previous clinical evidence (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020;van de Poll-Franse et al, 2020;Gultekin et al, 2021;Mogami et al, 2021). The HADS (Hospital Anxiety and Depression Scale) questionnaire was used to measure variables related to psychological symptomatology.…”
Section: Data Collectionmentioning
confidence: 99%
“…The studied populations are heterogeneous (patients with cancer under active treatment or follow-up, long survivors, different types of tumors or tumor stage, etc. ), which make it difficult to compare or extrapolate conclusions (Agua et al, 2020;Letaief-Ksontini et al, 2020;Miaskowski et al, 2020;Swainston et al, 2020;. In this regard, rates of depression and anxiety in cancer patients reported during the COVID-19 pandemic vary widely between 11.8-35.3 and 9.9-69.2%, respectively (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;van de Poll-Franse et al, 2020;Gultekin et al, 2021;Mogami et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, female participants had higher post-traumatic stress than males conducted in China during the COVID-19 outbreak [48]. Regarding the cancer population, while some studies have reported that female cancer patients had higher depression and anxiety than male during the pandemic [7,8], there has been no difference between males and females in another study [49]. Since the STAI-I was not an outcome measure in these studies, it is difficult to compare our results with these studies.…”
Section: Discussionmentioning
confidence: 85%